Freedoms of intimacy and the Internet - Jean Chalaby (Communicare)
This article argues that new media often get involved in struggles for new rights. The nascent book was involved in the struggle for religious freedom, the press has been engaged in the struggle for fairer political regimes and the Internet is used today as an instrument for the advocacy of new liberties: the freedoms of intimacy. Communities and individuals seek to gain rights related to the needs and preferences derived from their self-identity. This article shows that the Internet is best suited to dealing with issues associated with the self and intimacy than are other media. Taking the example of sexual minorities who use cyberspace as an alternative public sphere, it argues that it is particularly well adapted to two key practices that are essential to communitybuilding and that can only take place in the public sphere: self-definition and political mobilization. The article also shows how public authorities have always tried to censor new media when used by minorities to demand new rights. It argues that censorship has become increasingly efficient and that today's new media face a new means of censorship in technology. The article illustrates the case with the rating and filtering software used to censor cyberspace. Finally, it claims that the fight for new rights is part of the process of individualization inherent to modernity.